Ehrlichia canis Infection in a Labrador Retriever Dog: A Case Report - Chandrakant, Bhand Akshata; Shukla, Ravi Mohan; Rathore , Garima; Chaudhary, Siddharth; Tanwar , Chand; Arif, Syed A.; Yadav , Indu (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
A six-year-old Labrador retriever dog with a history of fever, inappetence, and unilateral epistaxis was presented to the Referral Veterinary Clinical Complex, Indian Veterinary Research Institute, Izatnagar. Clinical examination revealed the dog had pyrexia, an enlarged peripheral lymph node, and the presence of ticks on the body. The dog was suspected of having a haemoprotozoan infection, and a thin peripheral blood smear was submitted to the Division of Parasitology, Indian Veterinary Research Institute, Izatanagar, Bareilly, for examination. A blood smear was screened for haemoprotozoan examination using Giemsa’s stain, which showed positivity for Ehrlichia canis. Treatment was initiated with Doxycycline at 10 mg/kg B.wt. orally once for 28 days, along with supportive therapy, which resulted in a significant improvement in the dog's condition. An incidence of E. canis was reported from the Bareilly district of Uttar Pradesh.